Les Monts d'Aubrac au Moyen Âge Genèse d'un monde agropastoral - Fau, Laurent (Documents d'archéologie française, 2006)
The Aubrac plateau and its foothills have been studied by a multi-disciplinary team of archaeologists, historians, ethnologists and environmentalists. This research has shown that the region, despite its reputation as a hostile environment for humans, has a surprisingly rich archaeological potential. Numerous written documents and an exceptionally well preserved environment allowed the spatiotemporal framework of this research to be defined. This work shows how the Domerie (hospital) of Aubrac, which amassed numerous pasturelands, fossilized the habitat since the High Middle Ages. It presents the forms of agropastoral habitats that existed during the 11th to 13th centuries, which is one of the major themes of this study. Through the study of permanent (was) and temporary (buron) agricultural exploitation sites, located between 1100 and 1300 m altitude, it contributes to our knowledge of a rural mountain society during the Middle Ages.